Current and Future Prospective of Lignin Derived Materials for the Removal of Toxic Dyes from Wastewater. Issue 5 (3rd September 2021) - Bhatia, Anubhuti; Koul, Pranesh; Dhadwal, Akanksha; Kaur, Kiranjit; Kumar, Ajay
Abstract: The availability of safe drinking water has become a significant concern for the survival of living organisms. With the advancement and rapid growth in industrialization, a large amount of effluent containing dyes is released into the water streams. The long lasting and resilient properties of dyes make them a risk to human health and the environment. Various remediation approaches and technologies that are cost and energy efficient are urgently required to treat dye effluent. Lignin based nanoparticles with exceptional adsorption capacity, cost efficiency, non-toxicity, and biodegradability are considered a better alternative for dye removal. The utilization of modified lignin supports the magnetic nanoparticles, mesoporous nanomaterials, hydrogels, and hybrid nanocomposites to remove industrial dyes in wastewater. This review emphasizes current progression and future prospects in the efficient usage of lignin-based nano-adsorbents, with a focus on lignin, its modification, and its application involving elimination of toxic dyes by adsorption. Furthermore, it examines current research papers for the extensively used adsorptive isotherms, interactions, characterization techniques, thermodynamics of various lignin nanoparticles, and photocatalytic degradation of various organic pollutants, listed for easy reference. Abbreviations: TiO2 : Titanium dioxide; ZnO: Zinc oxide; SrTiO3 : Strontium titanate; CdS: Cadmium sulphonate; g-C3 N4 : Graphitic carbon nitride; BiOCl: Bismuth oxychloride; WO3 : Tungsten trioxide; ZrO2 : Zirconium dioxide; FTIR: Fourier-transform infrared spectroscopy; XRD: X-ray diffraction; SEM: Scanning electron microscopy; TEM: Transmission electron microscopy; BET: Brunauer-Emmett-Teller. GRAPHICAL ABSTRACT: UF0001